Topic related video segmentation - Xie, Henry Cheng You (2013)
This report addresses the problem of recovering the person-of-interest in a broadcast video. This is extremely challenging due to the imaged appearance variation of the person-of-interest in the video. However, the abstraction of the meaningful data is somehow similar to a table of content; it can serve as a useful index table, enabling users to browse through huge amounts of data in a non-linear manner.